Pertanggungjawaban Penggunaan Unmanned Aerial Vehicle (UAV) Dalam Konflik Bersenjata Ditinjau Dari Hukum Humaniter Internasional - Febby Magdalena Huwae; Irma Halimah Hanafi; Johanis Steny Franco Peilouw (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Today there is one type of aircraft that is often used in war, namely the Unmanned Aerial Vehicle (UAV) or in Indonesian called the Unmanned Aircraft (PTA) which is better known as the Drone.Purposes of the Research: To find out how the regulation of Unmanned Aerial Vehicle (UAV) and how the accountability of parties using Unmanned Aerial Vehicle (UAV) in armed conflict from the use of unmanned aircraft in armed conflict. Methods of the Research: This research uses normative juridical law research, with primary and secondary legal materials as the source of the law. The problem approach used is the statute approach, the conceptual approach, and the case approach. Furthermore, it is analyzed qualitatively.Results of the Research: The result of this study is that the use of drones by the United States in Pakistan has resulted in hundreds or even thousands of civilian lives and caused unnecessary damage both materially and formally. In addition, the legality of the use of drones is also still in question because until now there has been no definite binding standard. In this study, the authors suggest that the making of rules regarding drones should be implemented immediately, this is in order to prevent violations of international humanitarian law and to protect the security of civilians so that they do not suffer or suffer losses caused by drones.